Measuring customer satisfaction with the controllable elements of the in-store shopping experience - N. S. Terblanche; C. Boshoff (South African Journal of Business Management, 2001)
Evidence from various sources suggests that satisfaction with the individual components of an in-store shopping experience will result in customer satisfaction which will lead to customer retention and loyalty over the long term. It is argued that the in-store shopping experience (ISE) at store level consists of a variety of different dimensions that can be controlled by the retailer. This study reports on two phases of a long-term study on the controllable elements of the in-store shopping experience. Closely following the guidelines for multi-item scale development suggested by Churchill (1979) and based on the results of two empirical surveys, it is concluded that there are five dimensions of importance to consumers when assessing their satisfaction with an in-store shopping experience. These dimensions are merchandise value, personal interaction, merchandise variety, internal store environment and complaint handling. The proposed instrument in its current form demonstrates high levels of reliability, discriminant validity, convergent validity and construct validity.
Keywords: 650